Identification of nutritional components in unripe and ripe Docynia delavayi (Franch.) Schneid fruit by widely targeted metabolomics - Chen, Can; Xia, Xi; Wang, Dawei (PeerJ, 2022)
Docynia delavayi (Franch.) Schneid is an evergreen tree with multiple benefits and high development and utilization value. The fruit is consumed as fresh and dry fruit, juices, and other products. However, it is unknown the chemical changes that occur upon fruit maturation. The metabolite content of unripe and ripe fruit was examined using UPLC-MS/MS technology based on a broadly targeted metabolome. We identified 477 metabolites, of which 130 differed between ripe and unripe fruit. These compounds are primarily involved in the biosynthesis of secondary metabolites, such as pantothenic acid, flavonoids, and amino acids. Moreover, in ripe fruit, there are 94 metabolites that are upregulated, particularly flavonoids and terpenoids. In comparison, compounds associated with sour flavors (amino acids, phenolic acids, organic acids) are down-regulated. Remarkably, these metabolites have a strong relationship with the medicinal properties of D. delavayi. This study provides a global perspective of the D. delavayi fruit metabolome and a comprehensive analysis of metabolomic variations during fruit development, thereby increasing the knowledge of the metabolic basis of important fruit quality traits in D. delavayi fruit.
Keywords: Docynia delavayi (Franch); Metabolites; PCA; OPLS-DA; UPLC-MS/MS; KEGG